Provision of Modular System Home for Post-Disaster Communities - Syaifuddin Zuhri; Imam Ghozali; Joumil Aidil Saifuddin (Nusantara Science and Technology Proceedings, 2022)
Disaster is a very sad condition for the victims of the disaster, which destroys, eliminates, and destroys all aspects of people's lives, even the lives of relatives affected by the disaster. The destruction of infrastructure, buildings, and houses experienced by the victims caused them to have no shelter and shelter for themselves and their relatives. The absence of shelter for them after the disaster will cause very worrying problems and will have a continued impact on their next life. Housing as a temporary shelter for them is a very urgent need and it is very important to be held quickly to meet the needs of their next life. The provision of fast housing for victims affected by disasters is the focus of this research. The method of providing fast homes with a modular system is a building method where building components are built based on module units. These modules are assembled and assembled for easy use and disassembly. This type of house is increasingly being adopted in many areas, especially in areas where there are many disasters, because of its speed and efficiency. In this study, the aesthetic aspects and the flexibility of the container are excluded, but the emphasis is on the availability of basic residential space and the arrangement of the basic space module. Therefore, various efforts have been made to meet user demands for different living spaces by using only a few module units using a one-room system consisting of a living room, kitchen, bathroom, and sleeping area sufficient to meet basic living needs. daily. The function of the building is divided into three zones: service, public, and private.